The EU as a Multilateral Rule Exporter: The Global Transfer of European Rules via International Organizations - Rousselin, Mathieu (2012)
Abstract: This working paper investigates the conditions which prompt a variety of non-EU states grouped within an international organization to adopt European rules or standards rather than any alternative rule or standard available for selection. The paper reviews the main conceptual frameworks from research on the bilateral transfer of European rules and highlights similarities between these and alternative explanatory models of rule transfer, diffusion or convergence found in the broader IR literature. After identifying the main differences between bilateral and multilateral rule transfer processes, the paper proposes theoretical amendments to capture the original forms and new channels via which the EU can either impose constraint or seek consent at the multilateral level. On this basis, two hypotheses are formulated whose plausibility is subsequently probed by means of four comparative case studies dedicated to the worldwide transfer or non-transfer of European rules via international